27j-4=13s-10

Simple and best practice solution for 27j-4=13s-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27j-4=13s-10 equation:


Simplifying
27j + -4 = 13s + -10

Reorder the terms:
-4 + 27j = 13s + -10

Reorder the terms:
-4 + 27j = -10 + 13s

Solving
-4 + 27j = -10 + 13s

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 27j = -10 + 4 + 13s

Combine like terms: -4 + 4 = 0
0 + 27j = -10 + 4 + 13s
27j = -10 + 4 + 13s

Combine like terms: -10 + 4 = -6
27j = -6 + 13s

Divide each side by '27'.
j = -0.2222222222 + 0.4814814815s

Simplifying
j = -0.2222222222 + 0.4814814815s

See similar equations:

| 16x-1=15x+5 | | -13m+15m=-10 | | y=1/2(2)-7 | | x/(-4)=-7-(-5) | | 4q+-2q+4q=-18 | | y=1/2(0)-7 | | 8RP^2=AP | | -7(x+9)+403=12+13 | | -6r+7r=-12 | | -11(x+11)+1020=27+25 | | 114=2x+4(2x+11) | | 8+(3+6)=8+n | | y=1/2(-2)-7 | | 29+6=13 | | 2(8x+56)=80 | | sin(3*x)+sin(x)=cos(x) | | 4(5x+25)=60 | | (9p-7q+9r)-2(-9p+8q-6r)= | | x^2-60=b | | 4x+1y=0 | | 15-40/p | | 4c-3c+2=17 | | 6(k-1)=-38 | | 17c-13c-3c=12 | | 1b+7=15 | | 6-8t=-26 | | 100+35m=50+35m | | 8(v-3)-2= | | 7-2z=-5 | | 27-(7b+14)=9-8(b+1) | | 9z+7=16 | | 36-5=m |

Equations solver categories